THE DEVELOPMENT OF ANDROID MOBILE LEARNING APPLICATION BASED ON ARDUINO PROJECTS FOR JUNIOR HIGH SCHOOL STUDENT - Darul Agustiana Ma'rifah, - (2018)
The uses of technology commonly exist and essential for nowadays live. Mobile learning is one of the learnings tools that is easily used in this era. The aim of mobile devices nowadays are improved, its function is enlarged because the mobile devices can be used anywhere and anytime to connect the information, processes, and communications. Students consider that the function of using mobile to their learning is more productive. Physics is one of study that students often confused and mistakenly judged as a difficult subject to be learned. The advanced technology used in teaching and learning intended the researcher to build a mobile learning application especially in physics materials that relate with the used of Arduino UNO in form of technology. Generally, the process of developing the mobile learning application consists of several steps: (1) the content analysis; (2) the material source analysis; (3) the user analysis; (4) the software necessity analysis; (5) the hardware necessity analysis; (6) the design stage of mobile learning application making which consists of learning materials, flowchart, storyboard, interface making and coding. The method that used in this research was descriptive. The participants were 22 students of private Junior High School in Bogor and 3 science teachers from each respectively Junior High School in Bandung and Bogor. The experts on content, language, and media were evaluated the mobile learning application. The result shows that the overall of mobile learning application based on Arduino UNO is adequately received a good evaluation from each aspect. The students and science teachers are greatly welcomed for its implementation.;--Penggunaan teknologi harfiahnya terbiasa hadir dan penting dalam kehidupan saat ini. Mobile Learning adalah salah satu alat pembelajaran yang mudah digunakan di era ini. Tujuan dari perangkat mobile saat ini sangat berkembang, fungsinya itu sendiri menjadi menyebar karena perangkat mobile dapat digunakan di mana saja dan kapan saja untuk menghubungkan informasi, proses, dan komunikasi. Siswa menganggap bahwa penggunaan seluler dapat meningkatkan pembelajaran menjadi lebih produktif. Fisika adalah salah satu pelajaran yang sering membingungkan dan dinilai siswa sebagai subjek yang sulit untuk dipelajari. Teknologi canggih yang digunakan dalam pengajaran dan pembelajaran membuat peneliti tertarik untuk mengembangkan Mobile Learning terutama dalam materi fisika yang berhubungan dengan penggunaan Arduino UNO dimana ada hubungan dengan teknologi didalamnya. Secara umum, proses pengembangan aplikasi pembelajaran mobile terdiri dari beberapa langkah: (1) analisis konten; (2) analisis sumber material; (3) analisis pengguna; (4) analisis kebutuhan perangkat lunak; (5) analisis kebutuhan perangkat keras; (6) tahap perancangan pembuatan aplikasi Mobile Learning yang terdiri dari materi pembelajaran, flowchart, storyboard, pembuatan interface dan tahap pengkodingan. Metode yang digunakan dalam penelitian ini adalah deskriptif. Subjek penelitian terdiri dari 22 siswa dari salah satu SMP Swasta di Bogor dan 3 guru mata pelajaran IPA dari masing-masing SMP di Bandung dan Bogor. Para ahli dalam bidang konten fisika, bahasa inggris, dan media teknologi mengevaluasi aplikasi Mobile Learning ini. Hasil penelitian menunjukkan bahwa keseluruhan aplikasi pembelajaran mobile berbasis Arduino UNO mendapat evaluasi yang baik.